1984
DOI: 10.1029/ja089ia10p09057
|View full text |Cite
|
Sign up to set email alerts
|

Thermospheric circulation, temperature, and compositional structure of the southern hemisphere polar cap during October–November 1981

Abstract: Thermospheric temperature, composition, and winds at F region heights over the southern hemisphere polar cap have been measured by the Dynamics Explorer 2 (DE 2) satellite during October–November 1981. Perigee of the DE 2 satellite during this period was over the southern hemisphere polar cap, and measurements made along 0900–2100 local time polar passes are used to determine the average universal time dependence of thermospheric properties for this local time slice. The F region wind vector is derived from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…In this paper, we present the momentum forces at high latitudes for a steady diurnally reproducible model solution that considers both solar forcing and forcing by magnetospheric convection with a 60 kV cross-tail potential. The TGCM was run for average geophysical conditions appropriate to October 21, 1981, a case that was considered previously by Hays et al [1983] and Roble et al [1984] for a comparison of model predictions with measurements made by the Dynamics Explorer over the southern hemisphere polar cap during late October and early November 1981. These previous studies have shown that the ion-drag force due to magnetospheric convection has a strong influence on the high-latitude thermospheric wind, temperature, and compositional structures.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we present the momentum forces at high latitudes for a steady diurnally reproducible model solution that considers both solar forcing and forcing by magnetospheric convection with a 60 kV cross-tail potential. The TGCM was run for average geophysical conditions appropriate to October 21, 1981, a case that was considered previously by Hays et al [1983] and Roble et al [1984] for a comparison of model predictions with measurements made by the Dynamics Explorer over the southern hemisphere polar cap during late October and early November 1981. These previous studies have shown that the ion-drag force due to magnetospheric convection has a strong influence on the high-latitude thermospheric wind, temperature, and compositional structures.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It was used to study the global circulation, temperature, and compositional structures for equinox conditions during solar cycle minimum and also to derive a globally averaged eddy diffusion coefficient for the lower thermosphere that brings the model calculations into agreement with observed compositional structure as inferred from the MSIS empirical model of Hedin et al [1977a, b]. Roble et al [1984] furthermore used the updated TGCM to study the therm0spheric circulation, temperature, and compositional structures of the southern hemisphere polar cap during the latter part of October and early part of November 1981 and compared the model calculations with observations made by the Dynamics Explorer satellite. Their results showed that the measured temperature, composition, and winds all display a universal time dependence that is due to the displacement between geomagnetic and geographic poles.…”
Section: Thermospheric General Circulation Modelmentioning
confidence: 99%
“…Many studies have shown that neutral dynamics behave similarly to the ion dynamics at high latitudes. A number of studies using Dynamics Explorer 2 (DE 2) data (e.g., Hays et al, 1984;Killeen et al, 1984McCormac et al, 1987;Thayer et al, 1987) and thermosphere general circulation models (TGCMse.g., Fuller-Rowell andRees, 1980, 1981;Dickinson et al, 1981;Roble et al, 1984) established that the highlatitude neutral circulation tends to follow that of the ions, including the changes resulting from variations in IMF and geomagnetic activity. There are some differences, such as the very weak dawn cell in the neutral circulation pattern and neutral wind speeds that are much slower than those of the ions, but the similarities are sufficiently great that neutral winds should affect the neutral gas in a similar manner to the way that ion drifts affect the ions.…”
Section: Introductionmentioning
confidence: 96%
“…Coupling between ionospheric electric fields and the neutral atmosphere is particularly strong in the F-region, where observations [e.g., Killeen et al, 1984] and numerical models [e.g., Rees et al, 1983;Roble et al, 1984] show that neutral winds can be driven to speeds • 50% of those of the largescale, electric field drifts VE. The numerical models show that large-scale, convection electric fields can also modify neutral winds in the conducting E-region of the ionosphere.…”
Section: Introductionmentioning
confidence: 99%